Sole proprietorships in Malaysia: a study on the level of tax compliance among micro-businesses - Hanippvya, Saravana (2020)
This study sought to examine the level of tax compliance among sole proprietors in Malaysia conducting micro-businesses. The study was conducted in a qualitative perspective in order to obtain in depth views of sole proprietors in Malaysia. This study used economic and non-economic factors that affects the level of tax compliance, specifically, behavioural intention, tax knowledge and trust in the system as determinants towards tax compliance. Five sole proprietors operating micro-businesses around Klang Valley were selected as research samples and interviews via questionnaires were used as research instruments. Overall, the findings indicate that majority of the respondents have no major reservations of the cost of taxation, fair knowledge in taxation although they still need assistance in understanding technical aspects of it, and a good impression on Government expenditures from the tax collected. The findings further suggest that there is a need for a better tax knowledge among sole proprietors in microbusinesses operating in the country and they also expect the country’s tax authority to provide assistance in this matter. Additional studies on the betterment of tax knowledge among sole proprietors and on the connection between the educational level of sole proprietors and tax knowledge are recommended.